Evaluation of Groundwater Potential Zone Using Remote Sensing and Geographical Information System: in Kaffa Zone, South Western Ethiopia - Azarias Ayele Woldegebriel; Temesgen Abeto Amibo; Abreham Bekele Bayu (Program Pascasarjana Universitas Sriwijaya, 2021)
This study focused on delineating the groundwater potential and recharge area for Kaffa Zone by the method of remote sensing and ArcGIS 10.4 software analysis techniques. There are six main influencing factors (rainfall, slope, land use/cover, lineaments, drainage density, and Lithology) selected for groundwater recharge zone mapping. The thematic maps were scanned, geo-referenced, and classified as suitable for groundwater using ArcGIS 10.4. The methods to assess the potential zone were using weight overlay analysis and hierarchy of analytical process algorithm. The result obtained the potential of ground water were discussed recharge zones into four major categories: very good, good, and moderate and low. This can help for better planning and management the potential resource of groundwater. The results analyzed the groundwater potential that were subdivided in to low, moderate, high, and very high groundwater potentials areas that cover 1664.1,7682.9, 958.27, and 192.78 km2 respectively. The prediction accuracy was checked based on the borehole yield observed and predicted data of respective locations within the selected area. The prediction accuracy obtained (68.42%) reflects that the present study's method was produced significantly reliable and precise results.